Hank The Cowdog: The Secret Laundry Monster Files - Book 39 - Erickson, John R.; 1943-; Holmes, Gerald L. (New York, 2002)
Hank the Cowdog and Deputy Drover investigate a monster that appears just as they are about to arrest Eddy the Rac for ripping one of Sally May's sheets while it hangs on the clothesline.
Keywords: Fiction; Humorous Stories; West (U.S.); Fiction; Dogs; Fiction; Raccoons; Ranch life; West (U.S.); Fiction